The effect of artificial intelligence on students learning outcomes and motivation in biology: A literature review - Fathimatuzzahra, Fathimatuzzahra; Gravita Widyana, Agustin; Fajarrianto, Faisal; Khairunnisa, Khairunnisa; Diah Ayu Dwi Puspita, Raysanda (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The transformation of education in the 21st century demands technology-based innovation to strengthen learning effectiveness, particularly in Biology, which contains abstract concepts and requires strong visualization. One innovation that plays a crucial role in this context is the use of Artificial Intelligence (AI), which can support concept visualization and adaptive learning interactions. This study aims to analyze the implications of Artificial Intelligence (AI) on student learning outcomes and motivation in Biology through the Systematic Literature Review (SLR) method. The article selection process was carried out systematically using the PRISMA model for publications published between 2020 and 2024 in the Google Scholar database, resulting in 10 relevant articles. The results of the content analysis showed that AI integration consistently had a positive impact on student conceptual understanding, motivation, and engagement in Biology learning. Various AI-based media, such as chatbots, Google Lens, SUNO AI, PlantNet, and digital e-modules, have proven effective as facilitators that support active, adaptive, and personalized learning. In addition to improving cognitive learning outcomes, the use of AI also contributes to increasing digital literacy and student self-confidence. Thus, it can be concluded that AI functions not only as a learning tool but also as a strategic pedagogical solution in creating a quality biology learning ecosystem in the era of Society 5.0.Abstrak. Transformasi pendidikan pada abad ke-21 menuntut adanya inovasi berbasis teknologi untuk memperkuat efektivitas pembelajaran, khususnya pada mata pelajaran Biologi yang memuat konsep-konsep abstrak dan membutuhkan visualisasi yang kuat. Salah satu inovasi yang berperan penting dalam konteks tersebut adalah pemanfaatan Artificial Intelligence (AI) yang mampu mendukung visualisasi konsep serta interaksi pembelajaran yang adaptif. Penelitian ini bertujuan untuk menganalisis implikasi Artificial Intelligence (AI) terhadap hasil belajar dan motivasi siswa pada mata pelajaran Biologi melalui metode Systematic Literature Review (SLR). Proses seleksi artikel dilakukan secara sistematis menggunakan model PRISMA terhadap publikasi yang terbit pada rentang tahun 2020–2024 di basis data Google Scholar, sehingga diperoleh 10 artikel yang relevan. Hasil analisis isi (content analysis) menunjukkan bahwa integrasi AI secara konsisten memberikan dampak positif terhadap pemahaman konsep, motivasi, dan keterlibatan siswa dalam pembelajaran Biologi. Berbagai media berbasis AI, seperti chatbots, Google Lens, SUNO AI, PlantNet, dan e-modul digital, terbukti efektif sebagai fasilitator yang mendukung pembelajaran aktif, adaptif, dan personal. Selain meningkatkan hasil belajar kognitif, pemanfaatan AI juga berkontribusi terhadap peningkatan literasi digital serta kepercayaan diri siswa. Dengan demikian, dapat disimpulkan bahwa AI tidak hanya berfungsi sebagai alat bantu pembelajaran, tetapi juga sebagai solusi pedagogis strategis dalam menciptakan ekosistem pembelajaran Biologi yang berkualitas di era Society 5.0.